Diversity and Seasonal Abundance of Phytoplankton in Govardhan Das Pond Chapra Bihar - Pandey, Dr. Manoj Kumar (International Journal of Pharmaceutical & Biological Archive, 2012)
Diversity and Seasonal Abundance of Phytoplankton in Govardhan Das Pond Chapra Bihar